Geotecnologias aplicadas ao ensino de geografia: uma proposição didático-pedagógica para estudantes da educação básica no município de Nova Palma/ RS - Habowski, Jhennifer Tais Vieira (2024)
Maps are important for teaching Geography and understanding space. Nowadays, it is common to find various cartographic elements and applications on mobile devices, such as food networks, transportation, and even social networks. Therefore, it is important to reflect on the use of these technologies in teaching Geography and think about how Collaborative Cartography can promote basic education and the learning of several students. Consequently, it becomes necessary to debate the use of geotechnologies in teaching Geography, in school Cartography, and in Cartographic Literacy and Literacy to support pedagogical practices, impact student learning, and social relations in a dynamic, critical, and participatory way. Geotechnologies are fundamental resources to facilitate the teaching-learning process. Therefore, the problem of this work is how Collaborative Cartography and/or geotechnologies can contribute to the teaching of Geography, addressing the methodological process of constructing a map, and the possibility of a critical understanding of its representative process. The objective of the work is to investigate the potential of geotechnologies and Collaborative Cartography for teaching Geography, identifying prior knowledge and proposing workshops using geotechnological tools applied to teaching.The work in question took place at the Escola Municipal de Ensino Fundamental Professora Cândida Zasso, in the municipality of Nova Palma, in Rio Grande do Sul. Four workshops with different themes were designed for 6th and 7th-year classes over three days. As a result, there is a discussion about the understanding of these maps and how students are included in this process, reflecting on the importance of training a critical citizen. Therefore, it is believed that these geotechnological tools presented were extremely important for teaching geography, enabling students to comprehend the elements of the map. It should be noted, however, that they do not necessarily achieve cartographic literacy, as this requires a process throughout the student's training. Nevertheless, through the use of these tools, it is possible to have a greater interpretation of a map and understand the relevance of critical thinking in the formation of a citizen. In addition to the use of collaborative mapping as an element to describe their vision of the environment and how they are inserted, establishing a relationship between society and nature, students become not just reproducers of information but protagonists of their stories on the map. Therefore, the research contributed to promoting literacy and cartographic literacy and opened up possibilities for new perspectives on Nova Palma by its participants.